2012
DOI: 10.1104/pp.112.199703
|View full text |Cite
|
Sign up to set email alerts
|

MdCOP1 Ubiquitin E3 Ligases Interact with MdMYB1 to Regulate Light-Induced Anthocyanin Biosynthesis and Red Fruit Coloration in Apple    

Abstract: MdMYB1 is a crucial regulator of light-induced anthocyanin biosynthesis and fruit coloration in apple (Malus domestica). In this study, it was found that MdMYB1 protein accumulated in the light but degraded via a ubiquitin-dependent pathway in the dark. Subsequently, the MdCOP1-1 and MdCOP1-2 genes were isolated from apple fruit peel and were functionally characterized in the Arabidopsis (Arabidopsis thaliana) cop1-4 mutant. Yeast (Saccharomyces cerevisiae) two-hybrid, bimolecular fluorescence complementation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
292
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(307 citation statements)
references
References 51 publications
13
292
2
Order By: Relevance
“…Anthocyanin accumulation has a great impact on fruit quality, and many genes involved in the regulation of anthocyanin biosynthesis have been identified in fruit species such as grape (Kobayashi et al, 2004), apple (Malus domestica; Takos et al, 2006;Espley et al, 2007;Li et al, 2012), and pear (Pyrus communis ;Feng et al, 2010). However, few studies have been reported on characterization of the UFGT and AOMT gene families in fruit trees.…”
mentioning
confidence: 99%
“…Anthocyanin accumulation has a great impact on fruit quality, and many genes involved in the regulation of anthocyanin biosynthesis have been identified in fruit species such as grape (Kobayashi et al, 2004), apple (Malus domestica; Takos et al, 2006;Espley et al, 2007;Li et al, 2012), and pear (Pyrus communis ;Feng et al, 2010). However, few studies have been reported on characterization of the UFGT and AOMT gene families in fruit trees.…”
mentioning
confidence: 99%
“…Anthocyanin accumulation is enhanced by ultraviolet-B light in apple [23][24][25] and red Chinese sand pear (P. pyrifolia) [26]. Blue light induces anthocyanin accumulation and expression of associated genes in apple fruits [27], strawberry (Fragaria × ananassa) fruits [28] and Chinese bayberry fruits [29].…”
Section: Shading Treatment Decreased Pigment Accumulationmentioning
confidence: 99%
“…However, recent studies on the regulation of flavonoid biosynthesis pathways suggest that posttranscriptional and posttranslational mechanisms also play significant roles in the regulation of metabolic pathways. [6][7][8][9][10] The UPS has been demonstrated to regulate the activities of key regulatory proteins, including GL3, EGL3, PAP1 and PAP2, in the Arabidopsis flavonoid pathway. 9, 10 Here we show that two additional TFs, TT8 and TTG1, in the pathway are also targeted for proteasomal degradation, suggesting that the activities of most, if not all, TFs in the ternary complex that regulate the flavonoid pathway in Arabidopsis are regulated by UPS.…”
mentioning
confidence: 99%
“…The R2R3MYBs, PAP1 and PAP2in Arabidopsis, and MdMYB1 in apple, are degraded in the dark by the UPS suggesting that the lightmediated anthocyanin accumulation in Arabidopsis and apple skin is due, at least in part, to the stabilization of these factors in light. 7,9 We have recently shown that the bHLH factors, GL3…”
mentioning
confidence: 99%
See 1 more Smart Citation